2017
DOI: 10.1111/sltb.12325
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Aggression and Suicide‐Related Behaviors in Children and Adolescents: A Review and Preliminary Meta‐Analysis

Abstract: The empirical literature on the association between reactive aggression and suicide-related behaviors in children and adolescents was reviewed. A narrative review of seven studies that met inclusion/exclusion criteria is followed by a preliminary meta-analysis to provide insight into the strength of the association between reactive aggression and suicide-related behaviors. Each of the seven studies reported a statistically significant association between reactive aggression and suicide-related behaviors, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…It is also worth noting that irritability and impulsive‐aggression have been found to be associated with depressive symptoms in previous studies (e.g., Stringaris, Maughan, Copeland, Costello, & Angold, ; Brent et al, ), suggesting that impulsive‐aggression could predict suicidal ideation, and not attempt. However, other studies found that irritability (Orri, Galera, et al, ) and impulsive‐aggression (Hartley, Pettit, & Castellanos, ) were associated with both ideation and attempts. Furthermore, other authors pointed out to impulsive traits as explanatory factors in the transition from ideation to attempt (O'Connor & Kirtley, ).…”
Section: Discussionmentioning
confidence: 91%
“…It is also worth noting that irritability and impulsive‐aggression have been found to be associated with depressive symptoms in previous studies (e.g., Stringaris, Maughan, Copeland, Costello, & Angold, ; Brent et al, ), suggesting that impulsive‐aggression could predict suicidal ideation, and not attempt. However, other studies found that irritability (Orri, Galera, et al, ) and impulsive‐aggression (Hartley, Pettit, & Castellanos, ) were associated with both ideation and attempts. Furthermore, other authors pointed out to impulsive traits as explanatory factors in the transition from ideation to attempt (O'Connor & Kirtley, ).…”
Section: Discussionmentioning
confidence: 91%
“…Reactive aggression (also known as impulsive aggression) refers to aggressive behavior in response to perceived threat or provocation and is the main type of aggressive behavior (Berkowitz, 1993). Reactive aggression can have a serious negative impact on the health and social adjustment of individuals, and this may induce a higher risk for internalized problems, such as anxiety and depression, and a higher risk of depressive disorder, substance abuse, and impaired social relationships, thereby increasing the risk of suicide (Hartley et al, 2018). Although reactive aggression exists across different age groups, it is prominent among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…This model conceptualizes two separate mechanisms leading to SA among adolescents. One pathway is through reactive self-directed aggression and impulsivity (Hartley, Pettit, & Castellanos, 2018), which may have underlying dysregulated serotonin metabolism (Apter et al, 1990) or nonconventionality with social norms (King et al, 2001). The other independent pathway is that of an internalizing process based on anxiety and depression that may be related to interpersonal distress (Rueger, Malecki, Pyun, Aycock, & Coyle, 2016).…”
Section: Introductionmentioning
confidence: 99%